Impact of Herbal Mix Incorporation on Biscuit Attributes: Impact of herbal mix on biscuit quality - Anuj Kumar; Sharma, Gopal Kumar; Vashishth , Rahul; Semwal, Anil Dutt; Devi , Hanjabam Mandakini (Journal of Cereal Research, 2025)
The increasing popularity of foods possessing additional health benefits has set new demands for snack foods including biscuits. These novel snacks while maintaining basic nutritional benefits, should also exhibit additional health benefits. Along these lines, the biscuit was utilized as a carrier for herbal-mix consisting of tulsi, ginger, and black pepper. The baking combination of 190°C for 10 min and herbal blend having ginger, tulsi and black pepper in the ratio of 5:2:1 was standardized after preliminary experimentation. Herbal mix and honey concentration in biscuits were optimized employing a two-factor response surface methodology experiment based on central composite rotatable design. The optimal formulation of biscuits could be prepared using 6.38 parts herbal-mix and 55 parts honey. In comparison to control biscuits, functional biscuits had significantly (p<0.05) higher phenolic content (100.66±10.81 mg/ ml) and DPPH inhibition activity (22.01±0.84 %). The incorporation led to a slight decrease in the thickness, diameter, and spread ratio along with a modest increase in the textural hardness of the developed biscuits. The addition of herbal mix caused a decrease in the lightness value of the product. Functional biscuits developed possessed a good acceptance score (7.00±0.15) on the nine-point hedonic scale. The study justified the positive nutritional effect of herbal mix incorporation in biscuits. Keywords: Functional biscuits, herbal mix, antioxidative capacity, response surface methodology